STRATEGI PENGUATAN PERENCANAAN DAN PENGANGGARAN DI PROVINSI KEPULAUAN BANGKA BELITUNG DALAM MENANGGULANGAN KEMISKINAN - Wijaya, Novita Frahesti Ade; Rachmina, Dwi; Sarma, Ma'mun (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2017)
ABSTRACTThe realization of the poverty level in Bangka Belitung Province from 2013 to 2015 fluctuated. The levels of poverty in 2013 and 2015 did not reach the target while that of 2014 reached it. This research aims to analyze the implementation of planning and budgeting and to formulate strategies for strengthening the planning and budgeting of Bangka Belitung Province in regards to poverty alleviation. The analyses were carried out using the qualitative and quantitative methods. This research used primary and secondary data, and the determination of samples was conducted using a purpossive sampling technique. The results of the research show that (1) the level of planning and budgeting implementation in Bangka Belitung Province in poverty alleviation in the year of 2013-2015 was moderate with low competence variable of human resource, and this needs to be improved; (2) the internal and external matrices of the governmental policy of Bangka Belitung Provincial in supporting poverty alleviation with weighted score data of 2.354 and 3.055 were in quadrant II that is grow and build through intensive and integrated strategy; (3) the main strategy that must be implemented is to improve the support of local and central government policies in human resources development and planner apparatus to facilitate poverty alleviation. Implementation that can be conducted is the capacity building program of the planner apparatus for the period of 2018-2022.Keywords: integrated strategy, intensive strategy, implementation level, povertyABSTRAKRealisasi tingkat kemiskinan di Provinsi Kepuluan Bangka Belitung dari tahun 2013-2015 bersifat fluktuatif. Tingkat kemiskinan tahun 2013 dan 2015 tidak mencapai target, sedangkan tahun 2014 telah mencapai target. Penelitian ini menggunakan data primer dan sekunder. Penentuan sampel dipilih secara sengaja. Metode analisis yang digunakan adalah kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa (1) tingkat implementasi perencanaan dan penganggaran di Provinsi Kepulauan Bangka Belitung dalam penanggulangan kemiskinan tahun 2013-2015 adalah sedang dengan variabel kompetensi SDM rendah dan masih harus dilakukan perbaikan; (2) matriks internal dan eksternal kebijakan Pemerintah Provinsi Kepulauan Bangka Belitung dalam mendukung penanggulangan kemiskinan dengan data skor terbobot 2.354 dan 3.055 berada pada kuadran II grow and build melalui strategi intensif dan terintegrasi; (3) strategi utama yang harus dilaksanakan adalah meningkatkan dukungan kebijakan Pemerintah Daerah dan Pusat dalam pembinaan dan pengembangan SDM aparatur perencana untuk mempermudah penanggulangan kemiskinan. Implementasi yang dapat dilaksanakan adalah program peningkatan kapasitas sumber daya aparatur perencana selama tahun 2018-2022.Kata kunci : strategi intensif, strategi terintegrasi, tingkat implementasi, kemiskinan